If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3.00(20 + x) = 0 (20 * 3.00 + x * 3.00) = 0 (60 + 3.00x) = 0 Solving 60 + 3.00x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + 3.00x = 0 + -60 Combine like terms: 60 + -60 = 0 0 + 3.00x = 0 + -60 3.00x = 0 + -60 Combine like terms: 0 + -60 = -60 3.00x = -60 Divide each side by '3.00'. x = -20 Simplifying x = -20
| 9x-(3x+30)=12 | | 23+2y-9=11y-14-5Y | | 105n=-140n | | .17(1.2)= | | 4(a-2)=3a | | 22-7x=111 | | -3(t-1)+6t=5t-1 | | 3(x-4)=8x-5-5x | | 7x+2-x=5+5x-2 | | -6x^2-10=0 | | 6x+4=4(x+3) | | -3x+5+4x=-5+22 | | 10=-6x^2 | | 6-4y=11-8y+4y | | 4x^7+6x^2=0 | | 20x-6=50x+12 | | 36-8m=8m-7m | | y+2.5=-8.5-7.6 | | -3x+21=4x | | 1320=-2x+1200 | | 1320=6x | | 5d^2-45=0 | | x^2-12x-12=0 | | 5u+4.6=10.6 | | -5y-1(5y-9)=1+2(8-y) | | 6(x+9)+2=-8(x-7)-9 | | 5(5y+4)-17=6(3y-3)-7 | | 4(3x+21)=24 | | 5x+1=4(x+5)+9 | | 8(x-11)-6=20x-190 | | 20+-25= | | -2(9n+4)=22-7n |